2019
DOI: 10.18502/ijph.v48i2.834
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Spinal Deformity and Plantar Pressure According to the Static Standing Posture of Female Adolescents with or without Idiopathic Scoliosis

Abstract: The abstract not available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Plantar pressure measurement and gait analysis are widely accepted as vital biomechanical parameters for quantitative assessment of human gait which can provide useful information on foot function and assist with the development of more effective preventive and interventional strategies [6][7][8][9]. Several studies have indicated that the center-of-pressure (COP) trajectory in patients with AIS is different from that in healthy controls [8,[10][11][12][13]. Some previous studies have shown a difference in gait patterns between adolescents with untreated AIS and their healthy peers; conversely, other studies found no significant differences in gait analyses [5,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Plantar pressure measurement and gait analysis are widely accepted as vital biomechanical parameters for quantitative assessment of human gait which can provide useful information on foot function and assist with the development of more effective preventive and interventional strategies [6][7][8][9]. Several studies have indicated that the center-of-pressure (COP) trajectory in patients with AIS is different from that in healthy controls [8,[10][11][12][13]. Some previous studies have shown a difference in gait patterns between adolescents with untreated AIS and their healthy peers; conversely, other studies found no significant differences in gait analyses [5,[14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…There are only few studies that emphasized the relationship between modified static plantar pressure parameters and scoliosis; most investigations highlighted the importance of center of pressure trajectory in gait [29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with AIS, the asymmetry of the spine due to scoliosis might result in an abnormal force on the pelvis. When the load of the upper limbs and spine was transferred to the lower limbs, the load on the lower limbs would be changed, which could lead to an asymmetric force on the left and right sides of the trunk, pelvis, lower limbs, and feet [37][38][39]. The asymmetric load and force on both sides of the body would lead to skeletal growth disorders, aggravating scoliosis.…”
Section: Discussionmentioning
confidence: 99%